Justice and Financial Market Allocation of the Social Costs of Business - Christensen, Sandra L. (Journal of business ethics, 2001)
Regulation is often applied to business behavior to ensure that the social costs of doing business are included in the cost and pricing structures of the firm. Because the consumer benefits from the transaction that generated the social costs, asking the consumer to bear the burden imposed by the transaction is fair. However, there may be a lack of Justice m the internal and external distribution of the social costs of doing business if consumers are the only party bearing that burden, or if the costs are being shifted to employees or taxpayers when a closer stakeholder is also benefiting from the transaction – the stockowner. A social justice perspective requires that those benefiting from a transaction share in the burdens of it. We propose that a Tobin-like tax on stock transactions might be a just means of achieving greater justice in the distribution of the social cost burden.